Higher Education Spending and Sustainable Development Dynamics in Iraq - Ameera K. Lafta (Indonesian Journal of Law and Economics Review, 2026)
General Background: Higher education is widely recognized as a strategic pillar for achieving sustainable development, particularly in developing and post-conflict economies. Specific Background: In Iraq, structural instability, regional disparities, and digital inequality raise questions about how higher education financing and digital infrastructure relate to sustainable development trajectories. Knowledge Gap: Limited empirical studies integrate asymmetric time-series modeling with spatial econometric analysis to capture both temporal and geographic disparities in Iraq. Aims: This study examines the dynamic and spatial relationships between higher education expenditure, internet penetration, macroeconomic variables, and sustainable development indicators during 2003–2024 using NARDL and spatial panel models. Results: Findings reveal asymmetric responses, where reductions in education spending correspond to larger developmental setbacks than gains associated with increases, alongside significant spatial spillovers across governorates. Governance quality and unemployment mediate these relationships. Novelty: The study integrates nonlinear dynamic modeling with spatial econometrics to reveal cumulative and geographically clustered development patterns. Implications: Stable education financing, digital inclusion strategies, and regionally differentiated policies are essential for balanced and sustained development planning in Iraq. Highlights: Education budget reductions correspond to deeper long-run developmental declines. Strong spatial spillovers link governorate-level education and development patterns. Governance quality and unemployment shape cumulative development dynamics. Keywords: Higher Education, Sustainable Development, NARDL Model, Spatial Econometrics, Digital Divide